2011
DOI: 10.1186/1746-6148-7-34
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma gallisepticum infection in the grey partridge Perdix perdix: outbreak description, histopathology, biochemistry and antioxidant parameters

Abstract: BackgroundThe grey partridge is an important game bird in Europe that has declined considerably over the last decades. The production and release of farm-bred birds can be threatened by infectious agents. The objective of this study was to describe the outbreak, pathology, and blood and tissue biochemical responses in a flock of grey partridges naturally infected with Mycoplasma gallisepticum.ResultsMorbidity and mortality rates were 100% and 60%, respectively. Necropsy revealed an accumulation of caseous exud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
24
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 41 publications
6
24
0
3
Order By: Relevance
“…The results of this study document the fact that the liver is a major detoxifying organ and the main source of ROS generation in birds (Paskova et al 2011;Vitula et al 2011). Therefore, it is the first organ to show damage.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The results of this study document the fact that the liver is a major detoxifying organ and the main source of ROS generation in birds (Paskova et al 2011;Vitula et al 2011). Therefore, it is the first organ to show damage.…”
Section: Discussionsupporting
confidence: 63%
“…Low doses of both toxicants and the short duration of sub-lethal exposure were probably within its detoxifying threshold. Differences in avian responses to toxic exposure may also be influenced by species-specific and tissuespecific susceptibility (Meteyer et al 2005;Hussain et al 2008;Vitula et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Histopathology of the infraorbital sinuses in the infected turkeys was very similar to that observed in grey partridges exposed to M. gallisepticum (Vitula et al, 2011).…”
Section: Discussionsupporting
confidence: 66%
“…The northeastern goldfinch (Carduelis yarrellii) is another fringillidae passerine that occurs naturally in this region. Vitula et al (2011) reported deaths provoked by respiratory problems caused by Mycoplasma gallisepticum in Perdix perdix, a bird from the same family as the domestic chicken and turkey. Poveda et al (1990) found Mycoplasma gallisepticum in samples of respiratory tract and tissues from quails (Coturnix coturnix) and peregrine falcons (Falco peregrinus).…”
Section: Discussionmentioning
confidence: 99%